38 Global Improvement and Patient Satisfaction: Results from a Long-term, Open-label, Rollover Study of Valbenazine in Tardive Dyskinesia. (12th March 2019) - Verghese, Cherian; Lindenmayer, Jean-Pierre; Marder, Stephen R.; Burke, Joshua; Jimenez, Roland; Yonan, Chuck; Farahmand, Khody; Siegert, Scott
Abstract: Objective: Valbenazine (VBZ) is a novel vesicular monoamine transporter 2 (VMAT2) inhibitor approved to treat tardive dyskinesia (TD) in adults. It has been evaluated in 2 long-term studies (KINECT 3, KINECT 4) in which participants received VBZ (40 or 80mg) for up to 48weeks. This long-term rollover study (NCT02736955) was conducted to evaluate global TD improvement and patient satisfaction with once-daily VBZ. Methods: Key eligibility criteria: age 18 to 85 years; completion of KINECT 3 or KINECT 4; maintenance medications (for schizophrenia, schizoaffective disorder, or mood disorder) at stable doses; Brief Psychiatric Rating Scale score <50; no significant risk of active suicidal ideation or behavior. Following washout of prior VBZ treatment (Weeks 48 to 52 of KINECT 3 and KINECT 4), participants were re-initiated at 40mg (4weeks) and escalated to 80mg based on tolerability and clinical assessment of TD; dose was reduced to 40mg if 80mg was not tolerated (80/40mg). If unable to tolerate the 40mg dose, the participant was discontinued. Participants received open-label VBZ for up to 72weeks or until commercial availability. Assessments included Clinical Global Impression of Severity-TD (CGIS-TD: range, 1["normal, not at all ill"] to 7["among the most extremely ill patient"]) and Patient Satisfaction Questionnaire (PSQ: range, 1["very satisfied"] to 5["very dissatisfied"]). Results: 160 participants with available data were included in analyses (40mg =35; 80mg =117; 80/40mg =8); 138 were receiving treatment when VBZ became commercially available. The percentages of participants who completed visits at Wks 12, 24, 36, and 48 were 96.3%, 78.1%, 56.9% and 35.0%, respectively. Few reached Wk 60 (n=4) or Wk 72 (n=0) due to commercial availability. The percentage of participants with CGIS-TD score ≤2 ("normal, not at all ill" or "borderline ill") increased from baseline (before restarting VBZ) (40mg, 5.7%; 80mg, 18.1%) to Wk 48 (40mg, 41.7%; 80mg, 74.4%). At baseline, almost all participants rated their prior VBZ experience with a PSQ score ≤2 ("very satisfied" or "somewhat satisfied") (40mg, 100%, 80mg, 99.1%). Similar results were seen at the Wk 48 visit, with most participants continuing to express satisfaction with VBZ (40mg, 100%; 80mg, 97.4%). Conclusions: A clinician-based global assessment indicated ongoing, meaningful TD improvements in adults who received once-daily VBZ in the current study. In participants treated for >1 year, continued patient satisfaction rates with VBZ were high. Funding Acknowledgements: Neurocrine Biosciences, Inc.